KARAKTERISTIK FUNGSIONAL TELUR INFERTIL SISA HASIL PENETASAN YANG DIFERMENTASI MENGGUNAKAN Saccharomyces cerevisiae PADA LEVEL YANG BERBEDA (Functional Characteristics of Egg Infertile Hatchery Remaining at Fermentation in Saccharomyces cerevisiae Using Different Level) - L. Amaliah; Nahariah Nahariah; H. Fattah; H. M. Ali (Jurnal Ilmu dan Teknologi Peternakan, 2017)
Infertile  eggs  obtained  from  hatchery  process  has  experienced  a  declined  characteristic  in the functional properties. The decrease is due to the storage and warming up during the hatching process. An attempt should be taken to improve it through a fermentation process. This study aimed to determine  the  functional  characteristics of    infertile  egg   which was  fermented using different levels of Saccharomyces cerevisiae. This study was carried out according  to completely  randomized design  (CRD) with 4  treatments and 3  replications. The parameters measured were  the power of foam,  foam stability, coagulation  time and gel strength. The results showed  that  the  fermentation of  infertile eggs using different  levels of Saccharomyces cerevisiae   signifcantly (P<0.05) affected the foam power and foam stability and became highly signifcant (P<0.01) against coagulation time, but had no effects (P>0.05) on the gel strength. Fermentation using Saccharomyces cerevisiae at the level of 6% can maintain gel strength, improving foam, foam stability and coagulation time of infertile eggs obtained from the hatching process.